2007
DOI: 10.1158/1078-0432.ccr-06-2875
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Safety and Pharmacologic Study of a Twice Weekly Dosing Regimen of the Oral Taxane BMS-275183

Abstract: Purpose: BMS-275183, an orally administered C-4 methyl carbonate paclitaxel analogue, showed promising activity in a phase I trial investigating a weekly treatment regimen, but was associated with a relatively high incidence of neuropathic side effects.The current dose escalation phase I trial was initiated to investigate whether twice weekly administration of BMS-275183 would improve its safety and tolerability. Additionally, the pharmacokinetics and possible antitumor activity were studied. Experimental Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
(21 reference statements)
1
23
1
Order By: Relevance
“…The relatively high interpatient variability for BMS-275183 observed in this trial is not unprecedented and was also found in our previous studies (1,12). This may be due to variation in the absorption of the drug, combined with individual differences in metabolism.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The relatively high interpatient variability for BMS-275183 observed in this trial is not unprecedented and was also found in our previous studies (1,12). This may be due to variation in the absorption of the drug, combined with individual differences in metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…This lower dose may explain the apparent better tolerability observed in the present trial. A third phase I trial with BMS-275183 was conducted, investigating a twice-weekly dosing regimen (12). From this latter study, it was concluded that BMS-275183 is preferably given in a twice-weekly schedule.…”
Section: Discussionmentioning
confidence: 99%
“…BMS-275183 was synthesized as a part of a program to identify taxanes with potential for oral use in the treatment of cancers (Bröker et al, 2007). The compound is a C-4 methyl carbonate analog of paclitaxel that contains additional modifications in the side chain where the two phenyl groups of paclitaxel were replaced by t-butyl groups (Bröker et al, 2007).…”
Section: -Tert-butyl-3-n-tert-butyloxycarbonyl-4-deacetyl-3-dephenylmentioning
confidence: 99%
“…The compound is a C-4 methyl carbonate analog of paclitaxel that contains additional modifications in the side chain where the two phenyl groups of paclitaxel were replaced by t-butyl groups (Bröker et al, 2007). BMS-275183 exhibited good oral bioavailability in both rat and dog and showed antitumor activity comparable with intravenous paclitaxel (Frapolli et al, 2006).…”
Section: M20b M21 M22 and M23mentioning
confidence: 99%
See 1 more Smart Citation